2016
DOI: 10.1248/bpb.b15-00797
|View full text |Cite
|
Sign up to set email alerts
|

Daily Review of Antimicrobial Use Facilitates the Early Optimization of Antimicrobial Therapy and Improves Clinical Outcomes of Patients with Bloodstream Infections

Abstract: Insufficient information is available to confirm the beneficial effects of implementing an antimicrobial stewardship program in reducing mortality of patients with bloodstream infections. A single institutional cohort study was conducted to evaluate clinical outcomes after implementation of a daily review of antimicrobials used to treat patients with bloodstream infections. Subjects were allocated to groups receiving either intervention or nonintervention. After implementation of an antimicrobial stewardship p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 24 publications
0
11
0
1
Order By: Relevance
“…Compared to conventional methods, implementation of MALDI‐TOF MS reduced the time to effective antimicrobial therapy and optimal antimicrobial therapy by an average of 13.3 and 38.4 hours, respectively. While our previous study showed that implementation of an antimicrobial stewardship reduced the time to effective antimicrobial therapy in patients with bloodstream infections, additional implementation of MALDI‐TOF MS reduced these times even further. Several studies have demonstrated that rapid identification of the causative organism from blood culture bottles using MALDI‐TOF MS combined with AST reduces the time to effective antimicrobial therapy ranging from 9.7 to 34.3 hours and the time to optimal antimicrobial therapy ranging from 12 to 43 hours compared with conventional culture methods, which is comparable with the present results.…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations
“…Compared to conventional methods, implementation of MALDI‐TOF MS reduced the time to effective antimicrobial therapy and optimal antimicrobial therapy by an average of 13.3 and 38.4 hours, respectively. While our previous study showed that implementation of an antimicrobial stewardship reduced the time to effective antimicrobial therapy in patients with bloodstream infections, additional implementation of MALDI‐TOF MS reduced these times even further. Several studies have demonstrated that rapid identification of the causative organism from blood culture bottles using MALDI‐TOF MS combined with AST reduces the time to effective antimicrobial therapy ranging from 9.7 to 34.3 hours and the time to optimal antimicrobial therapy ranging from 12 to 43 hours compared with conventional culture methods, which is comparable with the present results.…”
Section: Discussionmentioning
confidence: 77%
“…The AST performed daily reviews of prescriptions for inpatients who received intravenous antimicrobials according to the prospective audit and feedback strategy. 17,18 This service was unchanged during both study periods. Briefly, we assembled a team comprising two physicians and three pharmacists who specialised in infectious diseases to implement the antimicrobial stewardship.…”
Section: Interventionmentioning
confidence: 93%
See 2 more Smart Citations
“…A series of strategies has been adopted to test new anti-infective agents in whole animal models such as Caenorhabditis elegans (C. elegans) [7]. Although the common screening method for new drugs using C. elegans is now widely recognized by researchers [8], the drug screening still focuses on the level of individual behavior (physiological indicators, mortality, etc.) in nematode infection models.…”
Section: Introductionmentioning
confidence: 99%